Analisis Reduplikasi pada Puisi Liburan Sekolah Karya Joko Pinurbo - Parasian, Nehemia Anugrah; Rizal, Billy Affandie; Nasution, Khairina; Deliana, Deliana; Widayati, Dwi (Aksara: Jurnal Bahasa dan Sastra, 2024)
Reduplication is the process of repeating a grammatical form, either fully or partially, whether with phoneme variation or not. The purpose of this research is to describe the forms of reduplication found in the poem School Vacation by Joko Pinurbo. The method used in this research is descriptive qualitative with data collection techniques (1) collecting data; (2) selecting data; and (3) categorizing data. The data analysis method in this research is as follows: data reduction, data presentation, and conclusion and verification. The results show that there are four types of reduplication in the poem Liburan Sekolah by Joko Pinurbo, including: (1) full reduplication, such as jalan-jalan, pelan-pelan, henti-henti, malam-malam, remang-remang, ketawa-ketawa, kepingan-kepingan, cari-cari, duduk-duduk, kata-kata, diam-diam, buku-buku, lelaki; (2) partial reduplication, such as berangsur-angsur, memecah-mecah, kenang-kenangan, melihat-lihat, membuka-buka, berdenyit-denyit, dibuat-buat, dikoyak-koyak; (3) reduplication of affixation, namely disipit-sipitkan; and (4) reduplication of phoneme change, namely seluk-beluk.Keywords: linguistic analysis, reduplication, morphology, poetry, joko pinurbo